Preparation and characterization of activated carbon derived from municipal wastewater treatment plant sewage sludge via carbonization and activation using superheated steam - Siajam, Shamsul Izhar; Sabli, Nordin (Yildiz Technical Univ, 2024)
Sewage sludge was converted into activated carbon (AC) by reacting the sewage sludge with superheated steam via carbonization and activation processes in a rotary kiln. The produced AC were analyzed for their physical properties and adsorption capacity, and the effect of carbonization and activation temperature were studied. The sewage sludge was carbonized at 400°C and activated between 500°C to 900°C for 1h. The AC was characterized using proximate analysis, BET, FTIR, SEM, and XRD. Its performance as an adsorbent was conducted using methylene blue. Activation at 800°C gave the most positive characterization results. Its proximate analysis resulted in moisture, volatile matters, ashes, and fixed carbon of 0.89 wt%, 6.9 wt%, 80.5 wt% and 11.7 wt%, respectively. The BET surface area, micropore vol., total pore volume, and pore size were 50 m2g-1, 0.0093 cm3g-1, 0.45 cm3g-1, and 17.95 nm, respectively. The FTIR analysis showed that AC had many O-containing functional groups. All analyses proved that the material produced was analogous to activated carbon derived from coconut husk. The methylene blue adsorption test showed AC activated at 800°C has the highest percentage methylene blue removal rate (97%) compared to those activated at other temperatures. The superior removal is due to superheated steam at 800°C stimulating the AC pore development, which excluded oxygen from the system to prevent unnecessary burnt offs. In short, carbonization and activation processes at 800°C using superheated steam produced enhanced physicochemical properties of AC and are very promising as a new adsorbent in attempting to reduce municipal sewage sludge.